"Economic Development" and Gender Equality: Explaining Variations in the Gender Poverty Gap after Socialism. (5th May 2015) - Fodor, Eva; Horn, Daniel
Abstract : Using the 2008 cross-sectional wave of the Statistics on Income and Living Conditions (EU-SILC) survey and multilevel modeling techniques, this article explores the macro-level determinants of the gender-poverty gap in the ten post-socialist EU member states. In dialogue with the literature on the impact of economic development on gender inequality in Asia and Latin America, we find that fast-paced, foreign capital-led economic growth is associated with a larger gender-poverty gap in Central and Eastern Europe, while generous welfare policies, specifically higher levels of spending on pensions and family policies, are correlated with women's lower relative destitution. These findings evaluate the impact of neoliberal style "economic development" on gender inequality in a geopolitically specific context and suggest that structural adjustment and global market integration may exacerbate women's vulnerability even when they are well equipped with human capital and other resources to compete with men in the labor market. Utilizando la oleada transversal de la encuesta de Estadísticas de Ingresos y Condiciones de Vida (EU-SILC) del 2008 y a través de técnicas de modelización multinivel, este artículo explora los determinantes a nivel macro de la brecha de género y la pobreza en los diez estados post-socialistas miembros de la UE. Partiendo de la literatura sobre el impacto del desarrollo económico en la desigualdad de género en Asia y América Latina, encontramos que el rápido crecimiento económico asociado a capital extranjero está relacionado con una mayor brecha de género y pobreza en Europa Central y del Este. Sin embargo, se observa que unas políticas de bienestar más amplias, específicamente aquellas con niveles más altos de gasto en pensiones y políticas familiares, se correlacionan con una menor pobreza en las mujeres. Estos hallazgos muestran el impacto del "desarrollo económico" neoliberal en la desigualdad de género en un contexto geopolítico específico y sugieren que el ajuste estructural y la integración del mercado mundial pueden incrementar la vulnerabilidad de las mujeres, incluso cuando éstas cuentan con capital humano y otros recursos para competir con los hombres en el mercado de trabajo.